QUALITY AND HALAL URBAN FARMING ASSISTANCE AS AN EFFORT TO MAKE THE MBG (FREE NUTRITIOUS MEALS) PROGRAM AND FOOD SECURITY A SUCCESS FOR THE AISYIYAH REGIONAL LEADERSHIP OF EAST NUSA TENGGARA ACHIEVING GOALS 2 OF SDGS 2030 INDONESIA - Nurmalasari, Intan Rohma; A. Miftakhurohmat; Syarifa Ramadhani Nurbaya; Siti Halijah; Fauziyah Lamaya (Journal of Social Comunity Services, 2025)
Objective: This study addresses Goal 2 of the Sustainable Development Goals (SDGs) 2030, emphasizing food security and safety by enhancing integrated agricultural information and awareness among Aisyiyah female activists, particularly women farmers and MSME drivers. The focus is on improving knowledge regarding food safety in the Free Nutritious Food (MBG) program targeting Indonesian youth. Method: A hybrid approach, combining online and offline activities, was employed. The program included two main interventions: online assistance on halal and healthy food quality assurance, and offline training on formulating hydroponic nutrient solutions and tea compost bag techniques. Results: The program successfully raised awareness about the prevalence of food poisoning—nearly 20%—in the MBG program and addressed the low horticultural production in NTT due to the high cost and health risks of chemical hydroponic nutrients. Participants, particularly from Aisyiyah leadership in Oebobo, Kupang, showed improved knowledge and skills in producing safe and independent hydroponic nutrients. Novelty: The integration of halal food quality training with sustainable urban farming practices through customized hydroponic nutrient formulation represents an innovative community empowerment model that strengthens food security and public health resilience among women-led groups in Eastern Indonesia.